What are the key dimensions of organizational culture? Evidence from Indonesia - Johannes Buntoro Darmasetiawan; Rapina Rapina (Research Synergy Foundation, 2023)
Corporate culture will create peer pressure that will guide the behavior of organization members so that they will work with the same rhythm. The corporate culture is usually influenced by Top Management or by a charismatic founder, who the Top Management still decides to use his/ her ideas. The corporate culture itself is an abstract form; it is difficult to explain what kind of characteristics (colors) it has. Luckily, the